Digital Literacy Acceleration Workshop and Mentoring for MSMEs in Kedinding Urban Village, Surabaya - Novianti, Rini; Sulistyowati, Eny; Aurora, Laurencya (Sarana Ilmu Indonesia (salnesia), 2025)
Digital literacy acceleration workshop and mentoring are a form of community service from STIE IBMT lecturers to MSMEs partners. This program was carried out because digital literacy is a very important competency in the digital economy era. This community service program aimed to increase the skills of MSME partners in designing attractive packaging for their products and performing digital financial bookkeeping for their businesses. The implementation method began with a situation and needs analysis, preparation of materials (Canva and digital cash book tutorials), workshop, mentoring, and program evaluation. The program involved 28 MSME partners in Kedinding, Surabaya. It ran smoothly and successfully, as evidenced by the participants’ enthusiasm during interactive discussions and hands-on practice. Evaluation results showed an increase in participants’ digital literacy regarding packaging design and simple bookkeeping, from a pretest score of 53% to 81% in the posttest.